Navigating Multicultural Challenges: A Case Study on Children's Rights Neglect in Indonesian Higher Education Major Selection - Hermansyah, Hermansyah; Aqil, Muhammad (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This study examines the neglect of children's rights in the selection of university majors in Papua, Indonesia, focusing on how cultural factors influence decision-making processes and the implications for students' academic journeys. Using a qualitative case study approach, the research investigates the manifestations of rights neglect in educational environments and their impact on study completion. Data were collected through document analysis, in-depth interviews, and participant observation at higher education institutions in Papua. The findings reveal that neglect of children's rights frequently occurs within family and societal contexts, where academic major choices are often imposed without consideration of the child's interests and talents. Factors influencing major selection include parental pressure, social influence, and incompatible learning models, all of which are affected by the diverse cultural backgrounds present in Papua. The disregard for children's rights in major selection often results in academic difficulties, leading to major changes, extended study periods, and potential social stigma. This study emphasizes the importance of a multicultural approach in higher education that values cultural diversity while protecting individual student rights. The research provides insights for developing more inclusive and culturally responsive educational policies and practices in Indonesia's higher education system.